Effectivity of Group Counseling Service with Transactional Analysis Approach to Decrease Difficulty Of Students Interpersonal Communication - Fauziah, Restu; Ahmad, Riska; Nurfarhanah, Nurfarhanah; Ardi, Zadrian (Universitas Negeri Padang, 2023)
This research background is based on preliminary study of SMAN 15 Padang students. the first discovery showed there were many students has difficulty in interpersonal communication; in message delivery or unclear information and inproper information receiving, the delivered information hurt other people, and there was also different mind and opinion which caused conflict, and less of attitude implementery while comunicating. this research is aimed to (1) disclose the differences of interpersonal communication difficulty in experimental group students before and after joining group counseling using transactional analysis approach, (2) disclose differences of interpersonal communication difficulties analisis transaksional control grup students before and after joining group counseling, and (3) reveal differences in interpersonal communication difficulties of experimental group students who follow group counseling using a transactional analysis approach with group counseling without special treatment. This research used quantitative approach, with experimental method, while the chosen research design is quasi experimental design with non-equivalent control group design as the model. There were 10 groups of experiment samples and 10 people for group control. The sample used purposive sampling. The instrument that used for the research is a likert scale model, the data was analyzed by using Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov Two Independent Samples with SPSS 26.00 version. The result of research showed that (1) there were significant interpersonal communication difficulties in experimental group of students before and after group counseling treatment by using transactional analysis approach, (2) there were significant differences of interpersonal communication difficulties in experimental students group before and after group counseling treatment without special treatment, (3) there were significant differences of interpersonal communication difficulties in experimental students group which given counseling treatment by using transactional analysis approach and without special treatment. To conclude, group counseling by using transactional analysis approach is more effective to decrease students' interpersonal communication difficulties.